The Oxford Handbook of Food, Politics, and Society 2013
DOI: 10.1093/oxfordhb/9780195397772.013.005
|View full text |Cite
|
Sign up to set email alerts
|

The Poor, Malnutrition, Biofortification, and Biotechnology

Abstract: While less apparent than outright hunger or obesity, the lack of essential vitamins and minerals in people’s diets is one of the leading contributors to the global burden of disease. Current interventions, such as supplementation or fortification, are being implemented with varying success, but—while important—overall progress in the fight against micronutrient malnutrition has been limited. Biofortification, the breeding of crops for higher contents of vitamins and minerals, is a new approach to complement ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 125 publications
0
7
0
Order By: Relevance
“…The HarvestPlus program now has eight focal countries (Bangladesh, DR Congo, India, Nigeria, Pakistan, Rwanda, Uganda, and Zambia). Cumulatively, more than 150 biofortified varieties of 10 crops have been released in 30 countries to date bred through conventional plant breeding rather than transgenic (genetically modified) which has faced stiff opposition with respect to food consumption [13,60].…”
Section: Fortification Of Staple Crops Complementary Foods and Bmentioning
confidence: 99%
See 1 more Smart Citation
“…The HarvestPlus program now has eight focal countries (Bangladesh, DR Congo, India, Nigeria, Pakistan, Rwanda, Uganda, and Zambia). Cumulatively, more than 150 biofortified varieties of 10 crops have been released in 30 countries to date bred through conventional plant breeding rather than transgenic (genetically modified) which has faced stiff opposition with respect to food consumption [13,60].…”
Section: Fortification Of Staple Crops Complementary Foods and Bmentioning
confidence: 99%
“…Although some studies suggest that there is a major acceptance hurdle with acceptance of genetically modified biofortified crops, other studies have shown that: genetically modified crops did not generally encounter major reluctance from poor consumers as was the case in China for folate GM-rice and multi-micronutrient GM-rice (provitamin A, folate, and zinc) [51]. However, willingness to pay has been found to be higher with conventionally bred cassava (compared to GM-cassava according to [60,69]).…”
Section: Fortification Of Staple Crops Complementary Foods and Bmentioning
confidence: 99%
“…Those who suffer from hunger due to insufficient energy intake are easily recognizable because it causes wasting and stunting, however, lack of nutrients, may not be visible, but may have serious health consequences (Stein, 2014). Serious health consequences have been reported in low selenium areas of China and Eastern Siberia, where selenium deficiency causes endemic Keshan disease in the Keshan region of China.…”
Section: About the Reduction Of Selenium Malnutrition Using Biofortifmentioning
confidence: 99%
“…Genetic biofortification, in which the nutritional contribution of food crops is increased through plant breeding, is an agricultural strategy to reduce nutrient deficiencies, particularly among rural populations in developing countries [1]. This strategy requires that a crop biofortified with a specific nutrient is targeted to a population that is both deficient in that nutrient and likely to consume the biofortified crop in sufficient quantities to reduce the deficiency.…”
Section: Introductionmentioning
confidence: 99%